Induction of autolysis in nongrowing Escherichia coli. - Tuomanen, E (1986)
Unless relaxation of the stringent response is achieved, all nongrowing bacteria rapidly develop resistance to autolysis induced by a variety of agents, including all classes of cell wall synthesis inhibitors. We now describe inhibitors of cell wall synthesis which were unusual in that they could continue to effectively induce autolysis in relA+ Escherichia coli even after prolonged amino acid starvation. The process of cell wall degradation seems to be catalyzed by similar hydrolytic enzymes in nongrowing and growing cells, yet the activity of these new agents capable of inducing autolysis in the nongrowing relA+ cells did not involve relaxation of RNA or peptidoglycan synthesis. We propose that the suppression of autolysis characteristic of nongrowing cells can be bypassed by a novel mechanism of autolytic triggering which is independent of the relA locus.